Intra-Articular Therapies in the Treatment of Hand Osteoarthritis: A Systematic Literature Review - Kroon, Féline P. B. (Drugs Aging, 2015)
BACKGROUND: Local treatments to alleviate symptoms in hand osteoarthritis (OA) are preferred, especially in elderly patients with comorbidities. Therefore, we have summarized the benefits and harms of intra-articular (IA) therapies. METHODS: We conducted a systematic literature review until May 2015, including all controlled trials investigating efficacy or safety of any IA therapy in carpometacarpal (CMC) and interphalangeal (IP) OA compared with placebo or other treatments. Two authors independently selected trials and assessed risk of bias using the Cochrane tool. The main efficacy outcome was pain. We performed meta-analysis where appropriate. RESULTS: A total of 13 trials (864 patients) studying CMC (n = 11) and IP OA (n = 2) were included, comparing corticosteroids or hyaluronic acid (HA) versus placebo (n = 4 and n = 3), and corticosteroids versus HA (n = 6). Single studies investigated infliximab, dextrose, and different HAs. The overall risk of bias was unclear or high in most trials. Meta-analysis of two trials comparing corticosteroids with placebo in CMC OA showed no improvement in pain [mean difference −3.56, 95 % confidence interval (CI) −13.87 to 6.75, scale 0–100). HA also appeared not efficacious compared with placebo in CMC OA. One trial comparing corticosteroids with placebo in IP OA demonstrated significantly improved pain during movement. No convincing evidence for efficacy of corticosteroids or HA over the other or alternative therapies was found. Only local adverse events were reported. No specific IA therapy appeared more harmful than another. CONCLUSION: Despite a beneficial short-term safety profile, IA corticosteroids or HA do not appear more effective than placebo in CMC OA. The suggestion that IA corticosteroids might be efficacious in IP OA requires confirmation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40266-015-0330-5) contains supplementary material, which is available to authorized users.